1971
DOI: 10.1042/bj1230983
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lipid peroxidation on membrane-bound enzymes of the endoplasmic reticulum

Abstract: 1. Induction of the formation of lipid peroxide in suspensions of liver microsomal preparations by incubation with ascorbate or NADPH, or by treatment with ionizing radiation, leads to a marked decrease of the activity of glucose 6-phosphatase. 2. The effect of peroxidation can be imitated by treating microsomal suspensions with detergents such as deoxycholate or with phospholipases. 3. The substrate, glucose 6-phosphate, protects the glucose 6-phosphatase activity of microsomal preparations against peroxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
3

Year Published

1977
1977
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(42 citation statements)
references
References 8 publications
0
39
0
3
Order By: Relevance
“…In view of reports in the literature that certain proteins and enzymes are destroyed or inactivated as a result of direct contact with lipid peroxides (Wills, 1961(Wills, ,1971, we also explored the possibility that the endogenously produced peroxides themselves exert a direct inhibitory action on the enzymes which are listed in Table 1. For this purpose we used a suspension of freshly washed spermatozoa which was sonicated for 60 sec and centrifuged at 5000 g for 15 min.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In view of reports in the literature that certain proteins and enzymes are destroyed or inactivated as a result of direct contact with lipid peroxides (Wills, 1961(Wills, ,1971, we also explored the possibility that the endogenously produced peroxides themselves exert a direct inhibitory action on the enzymes which are listed in Table 1. For this purpose we used a suspension of freshly washed spermatozoa which was sonicated for 60 sec and centrifuged at 5000 g for 15 min.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies have shown that the formation of peroxides in spermatozoa is accompanied by loss of phospholipid from the membrane and a rapid decline in motility (Jones & Mann, 1973,1976 (Mann, 1964) Brown (1975), and /?-7V-acetylglucosaminidase by the procedure of Conchie, Findlay & Levvy (1959).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Hence an alteration of lipid metabo lism could have brought on enzymatic changes. Lipid peroxidation on membranes is a wellknown effect of the cellular influence of radia tion (19). It has been observed that the increase of peroxidation is connected with biochemical alterations resulting from a structural mem brane injury (2,5,10,19).…”
Section: Discussionmentioning
confidence: 99%
“…Lipid peroxidation on membranes is a wellknown effect of the cellular influence of radia tion (19). It has been observed that the increase of peroxidation is connected with biochemical alterations resulting from a structural mem brane injury (2,5,10,19). It is known that cysteamine is rapidly concentrated in the liver, and mainly on the membranes of mitochondria and endoplasmic reticulum (1).…”
Section: Discussionmentioning
confidence: 99%